ANALISIS FENOTIP DAN GENETIK AYAM TOLAKI PADA MASA PERTUMBUHAN - Rusli Badaruddin; Jafendi Hasoloan Purba Sidadolog; Tri Yuwanta (Buletin Peternakan, 2013)
Tolaki chicken is a local chicken of Konawe, South Konawe, outh-East Sulawesi. This study was aim to identifythe phenotype and genotype of Tolaki chickens in the growth stage. The data were collected from 5 of mating groups between 5 roosters and 15 hens. Every group consisted of 1 and 3 head and produced 144 chicks (78 males and 66 females). The feed was given ad-libitum. Data collection included the phenotype characteristic and body weight of 0 until 12 weeks ages. The data were analyzed using ANOVA with Nested (hierarchical structure) design to obtain thecomponents of variance. The components of variance were used for estimating genetic parameters especially the heritability of the growth phase of Tolaki chicken. The results indicated that the growth of male chicken was faster than a rooster chicken. The heritability of growth trait based on the sire variance component (ĥ2 s) was high and had positive value at 0 to 12 weeks age.(Keywords: Chicken Tolaki, Genotype, Growth, Heritability, henotypes)